Expedient Synthesis of 6-Acylindolo[1,2-a]quinoxalines - Trawczyński, Adam; Telega, Magdalena; Wróbel, Zbigniew (Synlett, 2015)
A novel route leading to 6-acylindolo[1,2-a]quinoxalines involving condensation of N-(2-iodoaryl)-2-nitrosoanilines with β-diketones followed by Heck cyclization is described.
Keywords: cyclization; condensation; heterocycles; annulation; Heck reaction; indoles